Trade and Thy Neighbor's War - Qureshi, Mahvash (IMF Working Papers; Working Paper ;, 2009)
This paper examines the spatial dispersion effects of regional conflicts, defined as internal or external armed conflicts in contiguous states, on international trade. Our empirical findings-based on different measures of conflict constructed using alternate definitions of contiguity and conflict-reveal a significant collateral damage in terms of foregone trade as a result of spillovers from conflict in neighboring countries. The magnitude of this negative externality is somewhat larger for international conflicts than intrastate warfare, but about one-third of conflict in the host economies. Further, the impact is persistent-on average, it takes bilateral trade three years to recover from the end of intrastate conflicts in neighboring states, and five years from international conflicts. These findings are robust to alternate definitions of conflict, estimation methods, and specifications, and underscore the importance of taking into account spillover effects when estimating the economic costs of warfare.